Use of a Powered Stapling System for Minimally Invasive Lung Volume Reduction Surgery: Results of a Prospective Double-Blind Single-Center Randomized Trial - Akil, Ali; Semik, Michael; Freermann, Stefan; Reichelt, Jan; Redwan, Bassam; Görlich, Dennis; Fischer, Stefan (The Thoracic and Cardiovascular Surgeon, 2019)
Background Video-assisted thoracoscopic surgery (VATS)-lung volume reduction surgery (LVRS) represents an important treatment option for patients with advanced lung emphysema. For VATS lung resection, endoscopic staplers are routinely used. Recently, a new generation of electronically powered stapling systems was developed. In this study, the iDrive powered stapling system (Covidien, Germany) was first tested during VATS-LVRS and compared with a non-electronic conventional device.Methods Forty patients with advanced emphysema were enrolled in a prospective randomized trial. All patients underwent bilateral VATS-LVRS. Patients were randomized for iDrive use on the right lung (n = 20) or left lung resection (n = 20). A conventional endoscopic stapler (EndoGIA, Covidien) was used for contralateral resection in same patients. Therefore, 40 resections were performed with the iDrive and 40 with the EndoGIA. The duration of surgery, air leakage after extubation, and on postoperative day 1 (POD1), as well as length of chest tube therapy, were documented.Results The application of the new system was uneventful. Mean duration of surgery was 52 ± 2.5 minute in the iDrive group compared with 54 ± 3.8 minute in the EndoGIA-group (p = 0.5). After extubation, the mean air leakage in the iDrive-group did not differ significantly from that in the EndoGIA-group (p = 0.6). This was also observed on POD1 (p = 0.7). Moreover, length of drainage therapy also did not show significant differences between both groups (p = 0.6).Conclusion The iDrive powered stapling system offers one-handed, push-button operation, which eliminates the manual firing force and possibly enables more precise resection. In the current study, the novel system led to comparable results with the conventional mechanical stapler without any disadvantages in patients undergoing bilateral VATS-LVRS.
Keywords: linear stapling device; lung volume reduction surgery; lung emphysema; video assisted thoracoscopic surgery